2015
DOI: 10.1111/ncn3.179
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of zonisamide monotherapy in de novo patients with early Parkinson's disease

Abstract: Background Little is known about single administration of zonisamide in Parkinson's disease patients. Aim We aimed to evaluate the therapeutic effects of zonisamide monotherapy in early Parkinson's disease patients. Methods A total of 10 untreated (de novo) patients with Yahr stage I or II participated. Zonisamide was given at a daily dose of 25 mg for 1 month and increased to 50 mg for the next 2 months. Unified Parkinson's Disease Rating Scale parts I–IV and tremor‐related Unified Parkinson's Disease Rating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In 2009, ZNS was approved as an anti-PD drug that was an adjunctive therapy for PD in Japan. ZNS monotherapy ameliorated motor and sleep dysfunction in de novo patients with early-stage PD [14]. Previous experimental studies also revealed that ZNS attenuated loss of dopaminergic neurons in animal models of PD [15][16][17][18].…”
Section: Introductionmentioning
confidence: 82%
“…In 2009, ZNS was approved as an anti-PD drug that was an adjunctive therapy for PD in Japan. ZNS monotherapy ameliorated motor and sleep dysfunction in de novo patients with early-stage PD [14]. Previous experimental studies also revealed that ZNS attenuated loss of dopaminergic neurons in animal models of PD [15][16][17][18].…”
Section: Introductionmentioning
confidence: 82%
“…Now, zonisamide is approved as an adjunctive treatment in patients with advanced PD who show insufficient response to levodopa treatment. Moreover, recently, it has been reported that zonisamide monotherapy is effective for treatment in de novo patients with early PD [8].…”
Section: Introductionmentioning
confidence: 99%
“…ZNS, 1,2-benzisoxazole-3-methanesulfonamide, has been used for more than 20 years as an anti-epileptic drug in Japan (35). This medication was reported to ameliorate motor symptoms on UPDRS part III in PD patients (36-38). In 2009, ZNS was approved as an adjunctive therapy for Japanese PD patients.…”
Section: Dat Binding Modulation After Anti-pd Medicationsmentioning
confidence: 99%